Identification and Assessment of Children with Special Needs in Regular Schools - Maulana, Edi Sujati; Holidah, Siti Dedah; Isnarabani, Isnarabani; Rochyadi, Endang; Aprillia, Imas Diana; Susetyo, Budi (Angstrom Centre of Education, 2024)
This research aims to identify students with special needs, create their profiles, and design appropriate intervention programs. A qualitative method with a case study design was used with data collection instruments in the form of observation, documentation and interviews. Research subjects included school principals, teachers, regular students, children with special needs, and parents. The research was conducted in class IV of SDN Purwasari, Subang Regency, with a focus on identifying aspects of reading, writing and arithmetic. The results of the analysis show that one student, DI, has the lowest score in all three aspects. The next step is to prioritize the reading aspect because DI is not yet able to read. The reading assessment was carried out in three parts, and the results showed that DI still had difficulty answering questions or commands. Teachers are expected to design intervention programs on aspects of visual perception and phonological awareness before entering beginning reading material.